Multi-Country Evidenceon the Effects of Macroeconomic, Financial and Trade Policieson Efficiency of Resource Utilization in the Developing Countries - Odedokun, Mathew (IMF Working Papers; Working Paper ;, 1992)
This study examines the effects of selected policies on economic efficiency in 81 developing countries by pooling cross-country data over various subperiods between 1961-90. An incremental output-capital ratio is the measure of economic efficiency, while the policy variables include: export orientation, size of the public sector, directed credit program through development bank lendings, financial depth, inflation rate, real interest rate, and real exchange rate distortion. The export-orientation, financial depth, and real interest rate are found to promote economic efficiency, while other policy variables are found to hinder it.